2013
DOI: 10.4236/ojrad.2013.32014
|View full text |Cite
|
Sign up to set email alerts
|

Intra and Inter-Observer Reliability of Mobile Tablet PACS Viewer System vs. Standard PACS Viewing Station-Diagnosis of Acute Central Nervous System Events

Abstract: Background and Purpose: The display resolution of the Apple iPad® is 1024 × 768 pixels, which is greater than that required for generating the typical CT or MRI images. The purpose of this study is to determine if specific CT and MR sequences can be interpreted accurately on mobile device/PACS software platforms when compared to a traditional stationary high resolution monitor/PACS radiological workstation. If so, this allows radiologists to provide comparable interpretation as if they were onsite at an imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
(54 reference statements)
0
15
0
1
Order By: Relevance
“…17 Many authors identified the likely application of a tablet computer was for remote on-call interpretation of emergency imaging and chose cases and pathology relevant to this situation. 1,2,[8][9][10]15,18,20 Hence, the included studies were judged to have a high applicability to the review question. The exceptions were the study by Abboud et al, 17 which tested the reliability of TB screening; the use of emergency department physicians as the study readers by Park et al; 8 and the accuracy of diagnosing urolithiasis from the abdominal radiographs 16 (which has in a large part been replaced by CT imaging 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Many authors identified the likely application of a tablet computer was for remote on-call interpretation of emergency imaging and chose cases and pathology relevant to this situation. 1,2,[8][9][10]15,18,20 Hence, the included studies were judged to have a high applicability to the review question. The exceptions were the study by Abboud et al, 17 which tested the reliability of TB screening; the use of emergency department physicians as the study readers by Park et al; 8 and the accuracy of diagnosing urolithiasis from the abdominal radiographs 16 (which has in a large part been replaced by CT imaging 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,8 Limitations in network coverage and speed, potential effect of ambient lighting on diagnosis were also noted. 8,15,20 The inability to access clinical systems for referral information and prior studies 1 and the increased time to perform a read compared with primary workstation 19 were other limitations of using tablet computers. The portability and fast boot time were seen as the major advantage of tablet computers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For stereo calibration (i.e., alignment of color and depth data), default implementations are provided in the Microsoft Kinect for Windows SDK 4 and OpenNI. 5 This allows, the depth data to be transformed directly into the color camera coordinate system and the device continuously captures color and depth data in a uniform coordinate system.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…De Maio et al (2014) studied the accuracy of mobile diagnostics related to intra-articular knee pathology, concluding that an iPhone DICOM Viewer can be used and it is similar to that of a conventional radiology workstation. Bhatia et al (2013) also presented that mobile devices such as the Apple iPad can display adequate resolution of CT (computed tomography) and MRI (magnetic resonance imaging) sequences to accurately diagnose acute central nervous system injuries and other non-acute pathologies. John et al (2012) suggest that the emergency conditions commonly encountered in CT and MRI can be diagnosed using a portable device DICOM viewer with good concordance with the workstation evaluation.…”
Section: Mobile Application For Medical Diagnosismentioning
confidence: 99%